What price beauty! Tourists willingness-to-pay for cherry blossom preservation. (7th May 2019) - Sussan, Fiona; Nakagawa, Hideyuki
Abstract : Purpose: Mapping the intrinsic value of the art of architecture and the art of nature within the context of Kakunodate and the preservation of its samurai manors and Sakura heritage trees, this paper proposes that from the perception of tourists, the preservation of both items is important. Extending the psychology of pricing that is subject to consumers' preference and expectation to the context of valuation of cultural heritage assets, the purpose of this paper is to suggest that including the art of nature and the aesthetic of Sakura to the art of architecture (Samurai manors) will add more value to the cultural heritage of Kakunodate than when only the art of architecture is mentioned. Design/methodology/approach: This paper uses Contingency Valuation Method to solicit tourists willingness-to-pay to preserve the architecture and the nature in Kakunodate. The survey uses a double bounded dichotomous choice model to elicit the various levels of tourists preference in various scenarios. Response from more than 1, 000 tourists in three scenarios were collected. Through a maximum likelihood method and a subsequent truncated calculation, results are reported. Findings: The results support the conceptual argument that the art of nature adds value to the art of architecture only. Tourists are found to be willing to pay more to support both the architecture (samurai houses) and nature (cherry trees) than the samurai houses alone. Research limitations/implications: The research findings add to the inventory of research on prior works in heritage trees, conservation of trees and heritage tourism, and cultural heritage assets in general. The empirical findings support prior theoretical works that examined the relationship of nature and art, art and architecture, and architecture as visual consumption. Practical implications: The findings have managerial implications for policy makers relative to a possible increase of revenue by adding accompanying-nature component to focal architectural assets when soliciting funding support. Originality/value: The originality and this piece stems from extending trees as an art form in nature and its added value to architecture within the context of cultural heritage assets. The empirical findings add to the much discussed relationships among art, nature, and architecture.